Answer :

We have, ------(i)

Let =

[Since, ]

On putting the value of in Eq. (i), we get

------(ii)

We know that,

, xy

So, (ii) becomes,

=

=

or

or

or

or x = -1

or

For real solution, we have x = 0, -1.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers